Suitability of Muli Bamboo (Melocanna baccifera) for Making Bamboo Mat Plywood - Ashaduzzaman, M; Rana, R; Khan, MNH; Shams, MI (Bangladesh Journal of Scientific and Industrial Research, 2012)
This paper investigated the potentiality of muli (Melocanna baccifera) for making bamboo mat plywood. Bamboo mat plywood with the length, width and thickness of 2.4 m × 1.2 m × 7 mm was made using liquid urea formaldehyde resin. The physical and mechanical properties of such plywood were compared with the existing market plywood. The average density of bamboo mat plywood was much higher compared to the existing market plywood. The modulus of rupture (MOR) of bamboo mat plywood was 3 times and the modulus of elasticity (MOE) was 6 times higher compared to commercial (Bombax ceiba) plywood. Interestingly, the specific MOR and MOE were significantly higher than those of market plywood. The high strength values might be due to the long fiber length of the bamboo. Furthermore, the lamination of decorative thin garjan (Dipterocarpus turbinatus) veneer did not significantly reduce mechanical properties of the products. Bamboo plywood mat as well as garjan laminated bamboo mat plywood showed better performance in respect to thickness swelling, linear expansion and water absorption. Hence, muli bamboo can be a potential alternative source of raw material for the manufacture of plywood materials. Key words: Bamboo mat plywood; Density; Dimensional stability; Modulus of elasticity; Modulus of rupture DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9605 BJSIR 2011; 46(4): 543-548